(untitled) (Jurnal Ilmu Gizi dan Dietetik, 2026)
Nutritional status of students is an important indicator influenced by various factors, including dietary patterns and physical activity. Students, especially those aged 19–24 years, are still in a growth phase and require adequate nutrition and a healthy lifestyle to support academic productivity and long-term health. This study aims to determine the effect of dietary patterns and physical activity on the nutritional status of Biology Department students at the Faculty of Mathematics and Natural Sciences, State University of Makassar. This study is an analytic observational study with a cross-sectional approach involving 115 students. Data were collected using the FFQ questionnaire (dietary patterns), GPAQ questionnaire (physical activity), and Body Mass Index (BMI) measurements (nutritional status). Data analysis was performed using univariate, bivariate (Chi-square test), and multivariate (multiple linear regression) methods with SPSS 22. The majority of respondents had poor dietary patterns (53.9%) and high physical activity levels (63.5%). Chi-square test results showed a significant relationship between dietary patterns and physical activity with nutritional status (p=0.000). Multiple linear regression indicated that dietary patterns had a significant positive effect on nutritional status (B=0.006; t=4.283; p=0.000), while physical activity had a significant negative effect (B=-0.002; t=-11.439; p=0.000). The F value was 247.692, greater than the F table value of 3.08 (p=0.000), with an R² value of 0.816. There is a significant effect of dietary patterns and physical activity on the nutritional status of students. Improving dietary habits and increasing physical activity should be the focus of interventions to maintain optimal nutritional status.